Basic researchLoss of heterozygosity and microsatellite instability in the 3p24.2~3pter region in papillary thyroid carcinoma - Brzeziańska, Ewa; Migdalska-Sęk, Monika; Cyniak-Magierska, Anna; Koptas, Włodzimierz; Lewiński, Andrzej (Archives of Medical Science, 2007)
Introduction: The aim of this study was to analyse the loss of heterozygosity (LOH) and microsatellite instability (MSI) at the thyroid hormone receptor beta (THRB) locus (3p24.3) and in the 3p24.2~3pter region in human papillary thyroid carcinoma (PTC). Material and methods: Polymorphic cleaved amplified polymorphic sequence (CAPS) markers were used for cleaved amplified polymorphic sequence analysis to examine the THRB locus and microsatellite markers D3S1435, THRB, D3S1597 and D3S1304 were used to perform the innovative, PCR-based WAVE® Nucleic Acid Fragment Analysis to evaluate LOH/MSI presence in the 3p24.2~3pter region. Results: Twenty-three (23) PTC samples were used. Interestingly enough, only one [1] among 18 informative cases (1/18) presented with LOH at the THRB locus, while none of the same 18 cases revealed any trace of MSI. Moreover, we also observed a single polymorphism at the THRB gene, restricted to one of the used CAPS markers. Conclusions: Our results suggest that LOH and MSI in the 3p24.2~3pter region are not characteristic features in sporadic PTC.